Pain relief by targeting nonrestorative sleep in fibromyalgia: a phase 3 randomized trial of bedtime sublingual cyclobenzaprine - Lederman, Seth; Arnold, Lesley M; Vaughn, Ben; Engels, Jean M; Kelley, Mary; Sullivan, Gregory M (Pain medicine (Malden, Mass.), 2025)
Fibromyalgia is the prototypic nociplastic chronic pain syndrome, characterized by widespread pain, nonrestorative sleep, and fatigue. We evaluated efficacy and safety of bedtime TNX-102 SL (sublingual cyclobenzaprine) 5.6 mg for treatment of fibromyalgia. This phase 3, double-blind, multicenter, placebo-controlled trial randomized patients 1:1 to once-nightly TNX-102 SL 2.8 mg for 2 weeks, followed by 5.6 mg for 12 weeks, or to matching placebo (NCT05273749). The primary endpoint was change from baseline at week 14 in weekly average of daily diary pain intensity scores. Secondary endpoints included Patient Global Impression of Change, Fibromyalgia Impact Questionnaire (Revised) Symptoms and Function domains, Patient-Reported Outcomes Measurement Information System instruments for Sleep Disturbance and Fatigue, and daily diary sleep quality scores. Overall, 81.0% (n = 187/231) and 79.6% (n = 179/225) of patients receiving TNX-102 SL and placebo completed the trial, respectively. Treatment with TNX-102 SL vs placebo was associated with significantly greater reductions in the primary pain endpoint (P < 0.001; mean [SE], -1.8 [0.12] vs -1.2 [0.12]) and in each of the 6 secondary endpoints (P ≤ 0.001; all). The most common systemic treatment-emergent adverse events (TEAEs) with TNX-102 SL and placebo were COVID-19 (4.3% vs 3.1%, respectively), headache (3.0% vs 1.8%), and somnolence (3.0% vs 1.3%); the most common TEAEs overall were local administration-site reactions including oral hypoesthesia (23.4% vs 0.4%), product taste abnormal (11.3% vs 0.9%), and oral paresthesia (6.9% vs 0.9%), which were transient and self-limited. Bedtime TNX-102 SL treatment was associated with significant improvements in fibromyalgia symptoms and function and was well tolerated.